Euler equation errors - Lettau, Martin 1966-; Ludvigson, Sydney C. 1964- (National Bureau of Economic Research, 2005)
"Among the most important pieces of empirical evidence against the standard representative agent, consumption-based asset pricing paradigm are the formidable unconditional Euler equation errors the model produces for cross-sections of asset returns. Here we ask whether calibrated leading asset pricing models--specifically developed to address empirical puzzles associated with the standard paradigm--explain the mispricing of the standard consumption-based model when evaluated on cross-sections of asset returns. We find that, in many cases, they do not. We present several results. First, we show that if the true pricing kernel that sets the unconditional Euler equation errors to zero is jointly lognormally distributed with aggregate consumption and returns, such a kernel will not rationalize the magnitude of the pricing errors generated by the standard model, particularly when the curvature of utility is high. Second, we show that leading asset pricing models also do not explain the significant mispricing of the standard paradigm for plausibly calibrated sets of asset returns, even though in those models the pricing kernel, returns, and consumption are not jointly lognormally distributed. Third, in contrast to the above results, we provide one example of a limited participation/incomplete markets model capable of explaining larger pricing errors for the standard model; but we also find many examples of such models, in which the consumption of marginal assetholders behaves quite differently from per capita aggregate consumption, that do not explain the large Euler equation errors of the standard representative agent model"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Assets (Accounting) -- Prices -- Econometric models; Consumption (Economics) -- Econometric models